Sustainable Innovations in Textile Fibres - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights the innovations in textile fibres, that is the starting point of the supply chain. There are numerous innovations made in terms of making the existing fibres sustainable and also to discover new sustainable fibres. This book deals with those innovative sustainable textile fibres in detail. It also presents an overview of various current textile fibres, their issues associated with sustainability and how new, sustainable fibres overcome those issues. Finally it discusses the challenges and implications of these sustainable fibres on technical and economic fronts.
Sustainable Textile Fibres -- Natural Fibres, Their Properties and Surface Modifications Applied by Environmental Methods, Their Composites and Future -- Ecologically Friendly Fibres -- Fiber Extraction from Okra Plant Agricultural Wastes and Their Characterizations and Surface Modifications by Environmental Methods.
Keywords: Manufactures; Business logistics; Materials -- Analysis; Environmental chemistry; Industrial engineering; Production engineering; Chemistry, Technical; Machines, Tools, Processes; Supply Chain Management; Characterization and Analytical Technique; Environmental Chemistry; Industrial and Production Engineering; Industrial Chemistry